Assessment of the knowledge level on profession of physiotherapist among students of technical science and elderly persons - Kocjan, Janusz (Journal of Education, Health and Sport, 2017)
Introduction: Physiotherapy process enables the recovery of lost functions and return to maximum mobility. The range of physiotherapy includes procedures in situations where mobility and functioning are threatened by aging, injuries, diseases, a variety of disorders and conditions or environmental factors. Aim: The aim of the study was to determine the state of knowledge about the profession of physiotherapist among science students and people over 60 years of age. Material and methods: The study included 200 adult men and women in range of age: 21-75 years. The study was conducted on the basis of the author’s questionnaire containing 10 questions refers to: others possible physiotherapist work places, physiotherapist duties, action for which physiotherapist is entitled, relationship of physiotherapist profession with medicine and physical education, as well as, use of physiotherapy treatment in various fields of medicine. Results: Among the elderly, only 27% of respondents correctly distinguishes between the terms "physiotherapist" and "physical therapist." The vast majority of respondents see the need for rehabilitation on the orthopedic and neurological wards. The low level of knowledge refers to less popular specializations (gynecology, pulmunologia). The vast majority of respondents considered physiotherapy as a profession closer related to medical sciences than physical education. Conslusions: The results of the study indicate to the inadequate level of knowledge about profession of physiotherapist, especially among people over 60 years old.